Colloidal Synthesis of Ultrathin and Se-Rich V2Se9 Nanobelts as High-Performance Anode Materials for Li-Ion Batteries - Oh, Seungbae; Woo, Chaeheon; Ahn, Jungyoon; Kim, Tae Yeong; Dong, Xue; Kim, Yeongjin; Choi, Kyung Hwan; Chae, Sudong; Zhang, Xiaojie; Bang, Hyeon Seok; Kang, Jinsu; Jeon, Jiho; et al. (ACS Applied Materials and Interfaces, 2023)
In this study, the one-dimensional (1D) material V2Se9 was successfully synthesized using a colloidal method with VO(acac)2 and Se powder as precursors in a 1-octadecene solvent. The obtained colloidally synthesized V2Se9 (C-V2Se9) has an ultrathin nanobelt shape and a 4.5 times higher surface area compared with the bulk V2Se9, which is synthesized in a solid-state reaction as previously reported. In addition, all surfaces of C-V2Se9 are exposed to Se atoms, which is advantageous for storing Li through the conversion reaction into the Li2Se phase. Herein, the electrochemical performance of the C-V2Se9 anode material is evaluated; thus, the novelty of C-V2Se9 as a Se-rich 1D anode material is verified. The C-V2Se9 electrode exhibits a reversible capacity of 893.21 mA h g-1 and a Coulombic efficiency of 97.82% at the 100th cycle and excellent structural stability. Compared with the bulk V2Se9 electrode, the outstanding electrochemical performance of C-V2Se9 is attributed to its ultrathin nanobelt shape, high surface area, shorter Li diffusion length, and more electrochemically active sites. This work indicates the great potential of the Se-rich 1D material, C-V2Se9, as a post-transition metal dichalcogenide material for high-performance LIBs.
Keywords: 1D materials; Colloidal synthesis; High surface area; One-dimensional; One-dimensional van der waal material; Post-TMD material; Synthesised; Ultra-thin; V2se9 anode; Van der Waal; colloidal synthesis; Li-ion battery; one-dimensional van der Waals material; post-TMD materials; V2Se9 anode